2002
DOI: 10.1038/sj.mp.4001040
|View full text |Cite
|
Sign up to set email alerts
|

The substituted benzamides and their clinical potential on dysthymia and on the negative symptoms of schizophrenia

Abstract: In this paper the historical and scientific background that led to the use of substituted benzamides in two apparently unrelated clinical conditions namely dysthymic disorder and schizophrenia will be reviewed, in order to understand if a common mechanism of action may support this dual therapeutic indication. The dopaminergic antidepressant action of substituted benzamides such as sulpiride, has been proposed, since the late 1970s, by several authors and extensively explored in preclinical experiments by our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 89 publications
0
35
0
4
Order By: Relevance
“…20 It has been suggested that the clinical signs of chronic cannabis consumption may resemble negative symptoms of schizophrenia. 39 Several common symptomatologies do exist between schizophrenia and mood disorders. From a neuopharmacological standpoint, the psychoses of schizophrenia and the mania of bipolar disorder can both be treated with antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…20 It has been suggested that the clinical signs of chronic cannabis consumption may resemble negative symptoms of schizophrenia. 39 Several common symptomatologies do exist between schizophrenia and mood disorders. From a neuopharmacological standpoint, the psychoses of schizophrenia and the mania of bipolar disorder can both be treated with antipsychotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant action of AMS in extrastriatal areas became especially obvious at low concentrations (Möller, 2001;Xiberas et al, 2001). Although it was speculated that at these low dosages mainly D 3 autoreceptors in cortical areas were antagonized Pani and Gessa, 2002), the reason for the limbic selectivity of AMS remains unclear. Like its predecessor, sulpiride, it reveals some physicochemical peculiarities.…”
Section: Introductionmentioning
confidence: 99%
“…Striatal dopamine D 2 receptor occupancy in man was recently assessed by positron emission tomography (PET) (Martinot et al, 1996, Xiberas et al, 2001. It should be emphasized here that the striatum might be not the best region to elucidate the therapeutic action of AMS, which is suggested to be more active in extrastriatal areas Schoemaker et al, 1997;Pani and Gessa, 2002). This was corroborated by the study of Xiberas et al (2001), who revealed an accelerated occupancy of dopamine receptors in the extrastriatal compared with striatal areas at relatively low serum concentrations of AMS.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is likely that their rapid effects on monoamines may not be the direct cause of the clinical effects of antidepressants. Moreover, antidepressants of various classes, affecting serotonin, norepinephrine, or dopamine 7,8 have a common clinical effect. It has been hypothesized that the efficacy of the effects of various types of antidepressants after chronic treatment is due to their effects on new genomic targets.…”
Section: Identification Of Novel Therapeutic Targets For Drug Developmentioning
confidence: 99%